2012
DOI: 10.3168/jds.2011-5174
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide evaluation of quality and composition of colostrum on dairy farms in the United States

Abstract: The objective of this study was to characterize the quality of maternal colostrum (MC) fed to newborn dairy calves in the United States and identify the proportion of MC that meets industry standards for IgG concentration and total plate count (TPC). Samples of MC (n=827) were collected from 67 farms in 12 states between June and October 2010. Samples were collected from Holsteins (n=494), Jerseys (n=87), crossbred (n=7), and unidentified dairy cattle (n=239) from first (n=49), second (n=174), third or greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
222
27
30

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(321 citation statements)
references
References 32 publications
33
222
27
30
Order By: Relevance
“…The mean IgG concentration of samples in the present study (112651 g/l; mean6s.d.) was higher than that of some previous studies (Pritchett et al, 1991;Baumrucker et al, 2010;Morrill et al, 2012), but similar to that of others. Kehoe et al (2011) It is important to bear in mind that these studies have quantified colostral IgG using different laboratory analysis techniques; some have used radial immunodiffusion (Kehoe et al, 2011;Rivero et al, 2012) while others have used ELISA (Baumrucker et al, 2010;Nowak et al, 2012).…”
Section: Colostral Qualitysupporting
confidence: 87%
See 1 more Smart Citation
“…The mean IgG concentration of samples in the present study (112651 g/l; mean6s.d.) was higher than that of some previous studies (Pritchett et al, 1991;Baumrucker et al, 2010;Morrill et al, 2012), but similar to that of others. Kehoe et al (2011) It is important to bear in mind that these studies have quantified colostral IgG using different laboratory analysis techniques; some have used radial immunodiffusion (Kehoe et al, 2011;Rivero et al, 2012) while others have used ELISA (Baumrucker et al, 2010;Nowak et al, 2012).…”
Section: Colostral Qualitysupporting
confidence: 87%
“…Furthermore, differences in sample preparation between studies also exist. Baumrucker et al (2010) removed the colostral fat before analysis but Morrill et al (2012) did not. These differences in laboratory methods present difficulties when attempting to make true comparisons of colostral IgG concentrations across studies as variation in IgG concentrations measured may be partly attributable to the method used.…”
Section: Colostral Qualitymentioning
confidence: 99%
“…Thus, 77.4% of calves in the studied regions are likely to suffer failure of passive immunity transfer. In the United States, Morrill et al (2012) found that only 39.4% of 593 colostrum samples met both industry recommendations for colostrum quality. Such results are the evidence that more attention needs to be directed to management practices oriented towards cow handling in the last weeks before calving, as well as training and awareness of employees regarding the milking, storage, and supply of colostrum to feed newborn calves.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bacteria can bind to free immunoglobulins in the intestinal lumen and block absorption of these molecules by enterocytes (James and Polan, 1978) or stimulate the standstill of pinocytosis activity in enterocytes (James et al, 1981). Morrill et al (2012) evaluated colostrum from different North American regions and concluded that only 39% of samples had adequate IgG concentrations and ideal microbiological characteristics. Data in Brazil are scarce, and generally, evaluation of the quality of colostrum provided to newborns considers only the immunoglobulin (Ig) concentration, which is estimated using a colostrometer.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 60% of colostrum produced on US dairy farms does not meet the minimum immunological and bacteriological standards, i.e. >50 g.L −1 of IgG and a total plate count of <100,000 cfu.mL −1 , respectively (Morrill et al 2012). Limited work has been carried out investigating the efficacy of heat-treating colostrum from an immunological and bacteriological viewpoint.…”
Section: Introductionmentioning
confidence: 99%